Atomically thin WS2 nanosheets based gas sensor - Late, D. J.; Kanawade, R. V.; Kannan, P. K.; Rout, C. S. (Sensor Letters, 2016)
We report here the UV light and NO2 gas sensing properties of atomically thin few-layered WS2 nanosheets synthesized by a simple hydrothermal method. For the UV sensor, the response time was observed to be <15 s whereas the recovery time was <56 s. The Few layered WS2 nanosheets sensor devices were also tested for different concentration of NO2 gas at room temperature and 100 °C. The response time was observed to be <60 s whereas recovery time was >10 min. Further, the response and recovery time can be shortened by UV illumination or by removing the absorbed gas by heating the device at higher temperature. Our results open up the new avenues for gas sensors based on two-dimensional inorganic layered materials.